2002
DOI: 10.1177/153537020222700708
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Effects of Nicotine on the Pancreas: An Update

Abstract: Epidemiological evidence strongly suggests an association between cigarette smoking and pancreatic diseases. It is well recognized that nicotine, a major component in cigarette smoke, is an addictive agent and, therefore, reinforces smoking behavior. The current review update focuses on the genetics of nicotine dependence and its role on the development of pancreatic diseases. The role of smoking and nicotine in pancreatitis and pancreatic cancer development is also discussed. Exposure of laboratory animals to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 128 publications
2
66
1
Order By: Relevance
“…The proposed mechanisms underlying nicotine-induced acinar injury include intracellular calcium mobilization and activation of calmodulin-dependent protein kinases resulting in cytotoxicity and eventual cell death. 44 However, in this study, we did not observe similar morphological changes in the acinar cells of tobacco-treated WT mice. In addition to the species differences, the nicotine intake by mice in our study was found to be much lower, o0.6 mg per day of Snus-treated mice and o0.1 mg per day of TS-treated WT, compared with an estimate of 415 mg per day in Chowdhury's study.…”
Section: Carcinogenic Effects Of Tobacco In Chronic Pancreatitis Z Socontrasting
confidence: 73%
“…The proposed mechanisms underlying nicotine-induced acinar injury include intracellular calcium mobilization and activation of calmodulin-dependent protein kinases resulting in cytotoxicity and eventual cell death. 44 However, in this study, we did not observe similar morphological changes in the acinar cells of tobacco-treated WT mice. In addition to the species differences, the nicotine intake by mice in our study was found to be much lower, o0.6 mg per day of Snus-treated mice and o0.1 mg per day of TS-treated WT, compared with an estimate of 415 mg per day in Chowdhury's study.…”
Section: Carcinogenic Effects Of Tobacco In Chronic Pancreatitis Z Socontrasting
confidence: 73%
“…Thus, abdominal obesity, which is a strong risk factor for T2DM [37], is more prevalent in smokers. Furthermore, tobacco ingredients are likely to have toxic effects on the pancreas [38], a finding which is consistent with a higher risk of pancreatic cancer in smokers [39]. Furthermore, elevated levels of C-reactive protein [40,41] and plasma fibrinogen [30,40,41] have been found in smokers, suggesting that tobacco smoke might activate inflammation leading to T2DM.…”
Section: Causality Of the Association And Possible Pathwaysmentioning
confidence: 66%
“…Therefore, it is almost impossible to identify one substance responsible for one specific action because of the likely interactions of different chemicals, an uncomfortable situation for basic scientists. As a consequence, most studies either investigated the biological effect of tobacco smokederived substances with carcinogenic potential on the pancreas or investigated pancreatic alterations induced by pharmacologically active substances such as nicotine [8][9][10]. This strict separation of carcinogenic events from interference with regulatory events however, has to be undertaken with caution because recent studies indicate that carcinogenic substances as for instance 4-(methylnitrosamino)-1-(3-pyridil)-1-butanone (NNK) also exert widespread pharmacological actions [11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these carcinogenic events, the pharmacologically active substance nicotine contained in cigarette smoke has shown to induce morphologic pancreatic alterations as well [10,16]. The mechanism by which nicotine relays its effects on the pancreatic gland is believed to be mediated by nicotinergic acetylcholine receptors, which are ubiquitously expressed and are also involved physiologically in the regulation of pancreatic enzyme secretion [17].…”
Section: Introductionmentioning
confidence: 99%